EMMA : Researching the human reaction to fear,agony,empathy and how to provoke them using the VR technology as a medium - Neokleous, Constantinos (q, 2021)
The VR technology is the medium that has the ability to immerse you like no other, there are some VR games of the Horror genre, that has manage to give the filling of fear but most of them are relying on jump scares to accomplish the horror element, the environment, the atmosphere and the sound effects are sometimes overlooked by the developers and as a consequence the experience suffers. Therefore the main goal of this research is to produce a VR experience that will be able to immerse the user in a word where sadness, desperation and empathy will be the main filling of the user, to accomplished that there was a need to start with gathering the required data, to do that I had study video games and movies literature based on horror and fear, and how they have accomplish there task, after the required data where analysed I have implement that on the VR experience that was build using Unity engine.
Keywords: Human reaction; Fear; Emotions; VR